2018
DOI: 10.1177/0145721718784262
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement in Type 2 Diabetes: A Collaborative Community Health Initiative

Abstract: Purpose The purpose of this study was to describe the effects of an innovative rural community-based, diabetes self-management education and support (DSMES) program on patient behaviors and outcomes. Methods A 12-month pre-post study design with physiological data collection at program initiation, 16 weeks, and 6 and 12 months postenrollment was used for program assessment. The program consisted of an American Diabetes Association-accredited curriculum provided by the hospital and interfaced with a YMCA curric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Furthermore, community-based diabetes self-management programs have shown promise in improving diabetes-related knowledge and health outcomes [45, 46]. For example, in a pilot test and subsequent randomized control trial of a community-based program delivered by a team of nurses and peer educators, researchers observed significant improvement in diabetes knowledge among people with diabetes and mental health disorders after 60 weeks [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, community-based diabetes self-management programs have shown promise in improving diabetes-related knowledge and health outcomes [45, 46]. For example, in a pilot test and subsequent randomized control trial of a community-based program delivered by a team of nurses and peer educators, researchers observed significant improvement in diabetes knowledge among people with diabetes and mental health disorders after 60 weeks [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…28,30,33 Of the 14 studies measuring A1C, 9 demonstrated statistically significant reduction in A1C. 29,31,33,[37][38][39][40][41][42] Of the 9 studies measuring BP, 3 demonstrated statistically significant improvements in BP. 27,38,41 Three of the 6 studies measuring lipids demonstrated statistically significant improvements in lipids, 30,40,42 and 4 of the 5 studies measuring fasting glucose demonstrated statistically significant improvements in fasting glucose.…”
Section: Study Characteristics and Outcomes Of Studiesmentioning
confidence: 98%
“…[28][29][30][31][32][33][34][35][36][38][39][40] Four studies were conducted outside the US in the following countries: Belgium, 37 Dominican Republic, 41 India, 27 and Iran. 42 When looking at each study by community setting, 11 studies were conducted in a local community site, 28,30,31,[33][34][35]38,[40][41][42] 1 study was conducted in a community pharmacy, 37 2 studies were conducted at a community clinic, 29,32 and 2 studies were conducted in the home or a community site based on participant availability. 36,39 Additionally, Table 1 summarizes the type of intervention that was conducted as well as the impact on outcomes.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Positive effects of family social capital for persons with T2DM include improved self-management capabilities and glycemic control, reduced weight and A1C, fewer medications, and fewer emergency department visits. 13,[25][26][27] Mechanisms that may mediate the relationship between family social capital and health include the influence of social networks, connections through social engagement, and emotional, instrumental, and informational support. 24,28 Understanding how to increase family social capital in T2DM selfmanagement may provide meaningful information to inform interventions for MA adults with T2DM.…”
mentioning
confidence: 99%